He who was called (the merchant) among the scholars in Nishapur and an explanation of his spending impact on knowledge, according to what was stated in the book “The Context on the History of Nishapur” by the historian Abd al-Ghafer al-Nisaburi (d. 529 AH (Journal of the College of Basic Education, 2022)
This research is considered an academic study, carried out by the researcher to show the spending effects of scholarly merchants on knowledge and its people in the Nisaburi scholarly halls, and to reveal their scientific contributions in several arts, foremost of which are classification and teaching, and the same way in hinting at their attainment of religious titles commensurate with these contributions such as titles: ( Faqih, Muhaddith, Sheikh), according to what was stated in the book Al-Siyaq on the History of Nishapur by the historian Abd al-Ghafer al-Nisaburi (d. 529 AH / 1141 CE).